11 LONG-TERM OUTCOMES OF SINGLE VERSUS MULTIVESSEL STENTING IN A PUBLIC HEALTH SYSTEM PATIENT POPULATION WITH UNIFORM BARE METAL STENT SELECTION, ADJUNCTIVE GLYCOPROTEIN IIB/IIIA INHIBITION AND LONG-TERM DUAL ANTIPLATELET THERAPY. (1st March 2005) - Nathan, S.; Attanasio, S.; Amin, A.; Kumar, A.; Gupta, A.; Kelly, R. F.
Abstract : Background: Published data suggest that lower socioeconomic status may adversely impact health outcomes in patients with coronary artery disease. Data regarding post-PCI outcomes are particularly limited in this population. We assessed event-free survival in public health system (PHS) patients undergoing single (SV) vs multivessel (MV) PCI with procedural glycoprotein (Gp) IIb/IIIa inhibition and long-term dual antiplatelet therapy with aspirin and clopidogrel. Methods: 280 consecutive patients (205 SV, 75 MV) undergoing PCI at Cook County Hospital, with uniform Medtronic AVE bare metal stent use, procedural Gp IIb/IIIa inhibition and intended long-term ASA/clopidogrel use were followed as a prospective cohort for occurrence of the composite MACE endpoint (death, MI, urgent TVR) and all-cause mortality. Clinical, demographic and procedural data were compiled and analyzed with missing angiographic data adjudicated by blinded review. Kaplan-Meier life table analyses were performed for the cohort, using the Wilcoxon and log-rank tests for survivor functions. Results: Demographic variables and risk factors were similar between SV and MV groups except smoking (80.6% vs 19.4%, p<0.031) and family history of CAD (37.3% vs 24.4%, p = 0.02). PCI indications were comparably distributed between SV and MV groups. Overall 46% of patients presented with ACS/NSTEMI or STEMI. Procedural GpIIb/IIIa inhibition was used in 98.3% of patients and 73.3% of patients were on aspirin plus clopidogrel at long-term follow-up. The groups were similar with regard to stents per vessel and stented length per vessel but differed by total stents per patient (1.05 vs 1.79, p<0.001). Clinical follow-up (mean 329, max 780 days) was attained in 93.9% of patients. Overall 1 year event-free survival was 91.4%. MACE-free survival by Kaplan Meier analysis was similar between SV and MV cohorts at a total follow-up of 780 days (92.2% vs 90.7%, p = 0.66). Conclusions: Single and multivessel PCI with bare-metal stent use, adjunctive GPIIb/IIIa inhibition and long-term clopidogrel therapy was associated with excellent event-free survival in the PHS population studied. Despite a sizeable subset of high-risk patients, these estimates are comparable to historical, non-PHS control populations undergoing bare metal stenting.